2006
DOI: 10.1007/s00421-006-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a 5 × 6-s maximal cycling repeated-sprint test in trained female team-sport athletes

Abstract: The present study examined the reliability of work and power measures during a 5 x 6-s cycle ergometer test of repeated-sprint ability. Nine, well-trained, female soccer players performed five, 5 x 6-s repeated-sprint tests on a front-access cycle ergometer on separate days. Sprints were separated by 24 s of active recovery. Absolute measures of total work done (W (tot)), total peak power (PP(tot)), work done during sprint 1 (W (1)) and peak power output during sprint 1 (PP(1)) were recorded. Decrement scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 29 publications
6
38
0
Order By: Relevance
“…When co-ingestion was compared to sodium bicarbonate alone, we found no meaningful performance improvement in peak mechanical power ( The most surprising outcome of the present study was that all conditions reported a likely detrimental effect on fatigue index. Fatigue index data in the present study should be interpreted cautiously; we observed a coefficient of variation of 19.9% in our reliability study, which appears to be a consistent finding (Hughes et al, 2006;McGawley & Bishop, 2006;Oliver et al, 2006). A limitation to the present study was the failure to measure blood measurements of pH, bicarbonate, lactate and intramuscular phosphocreatine.…”
Section: Discussionsupporting
confidence: 81%
“…When co-ingestion was compared to sodium bicarbonate alone, we found no meaningful performance improvement in peak mechanical power ( The most surprising outcome of the present study was that all conditions reported a likely detrimental effect on fatigue index. Fatigue index data in the present study should be interpreted cautiously; we observed a coefficient of variation of 19.9% in our reliability study, which appears to be a consistent finding (Hughes et al, 2006;McGawley & Bishop, 2006;Oliver et al, 2006). A limitation to the present study was the failure to measure blood measurements of pH, bicarbonate, lactate and intramuscular phosphocreatine.…”
Section: Discussionsupporting
confidence: 81%
“…Otherwise, we considered that performance can also decline with the repetition of exhaustive exercises and subjects did not perform familiarization trials. This is a potential limitation, because the familiarization of subjects with the repeated-sprint test can also improves the reliability of work and power measures [43]. However, with regard to the lack of difference in the number of work periods completed between the 1 st and the 2 nd session, and given that the subjects took the NO 3 -supplementation and placebo in a randomized order, we are confident that the learning effect was minimal on the performance outcomes.…”
Section: Experimental and Methodological Considerationsmentioning
confidence: 93%
“…Reliability was defined as the extent to which the experimental trials yielded the same results on repeated trials. Coefficient of variation values were classed as good (< 5%), moderate (5-10%), or poor (> 10%) based upon values observed previously in maximal concentric cycling < 10 s [11,16,17]. Figure 1 shows the mean values (± SD) for peak PO and average PO across all trials.…”
Section: Statistical Analysesmentioning
confidence: 90%